EVALUASI LITERASI DIGITAL SISWA DALAM PEMBELAJARAN INFORMATIKA KELAS VIII DI SMP KATOLIK SANTO YOSEPH NAIKOTEN KUPANG - Saekoko, Jurni; Khatrin J. Taku Neno; Jhon Enstein (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to evaluate the level of digital literacy among eighth-grade students at SMP Katolik Santo Yoseph Naikoten Kupang and identify the determinant factors influencing it. Utilizing a qualitative approach with a CIPP (Context, Input, Process, Product) evaluation desing developed by stufflebeam, thi study analyzes the implementation of digital literacy amidst infrastructure limitations and strict school policies. Data were collected through classroom observatation. The results indicate thet students have achieved a proficient level in technical and operational digital literacy, demonstrating the ability to operate devices and utilize digital platforms for learning purposes. However, in the critical by instances of plagiarism, alack of proper citation, and communication ethics that reguire further improvement. Key obstacles include infrastructure constraints, such as the limited number of Chromebook and unstable internet access, as well as school policies that restrict device usege to informatics class hours only. This study conludes that the development of digital literacy reguires a paradigm shift from technical mastery alone towerd the reinforcement of digital ethics integrated across all subjects, along with more flexible school policies to support responsible digital exploration.